Design of a hierarchically structured hybrid material via in situ assembly of a silica aerogel into a wood cellular structure. Issue 67 (30th June 2016) - Sedighi Gilani, M.; Zhao, S.; Gaan, S.; Koebel, M. M.; Zimmermann, T.
Abstract : We present a route for incorporation of silica aerogel into wood cellular structure. Modification results in an improved dimensional stability and reduced water retention of the material, with lower thermal conductivity and total heat of combustion. Abstract : A novel hierarchically structured wood-templated silica aerogel hybrid material was synthesized through sol impregnation and in situ gelation within a Norway spruce wood scaffold. Following chemical modification and supercritical drying of the microstructured gel phase, the desired hybrid wood–aerogel composite was obtained. The developed method presents a new route for efficient incorporation of highly mesoporous low-density silica aerogel into cellular biomaterial structures without the need for pretreatments to access the complex cellular level network. In-depth characterization using microtomography and electron microscopy revealed that the mesoporous silica aerogel filled the wood lumina to a very large extent, whereas no silica was deposited inside the wood cell walls. The incorporation of the hydrophobic aerogel substructure within the wood microstructure resulted in an improved dimensional stability and reduced moisture retention of the hybrid material which may lead to improved durability at higher humidity. Furthermore, the super-insulating silica aerogel phase leads to lower thermal conductivity and total heat of combustion. This study is viewed as a proof of concept for the in situ preparation of natural bio template based hybrid aerogels, and will enable a new generation of multifunctional bioinspired materials with tailored physical properties and applications.